Multi-Objectives Optimization Of Energy Consumption Of IKM Bintulu Buildings Towards Energy Saving - Othman, Muhamad Naim (UTeM, 2017)
The power consumption of air conditioning and lamps in IKM Bintulu buildings contribute a high billing cost and power consumption of the total energy. The consumption is needed to ensure the comfort of working and learning environment for staffs and students as well. Hence, this project proposed a method called "Multi-Objective Optimization of Energy Consumption" in order to optimize the power consumption in the buildings without neglecting the comfort of the staffs and students called an occupants. The method applied the Genetic Algorithm (GA) to umavel the multi-objective optimization problem that involved the power consumption and the comfort of the 200 occupants. The method is focused on the room temperature (°C) and the light illumination (Lux). The experiments are conducted by using one air conditioning and 12 units of fluorescent lamps called 12 nos with 36 Watts rated in a 40 meter square (m2) room. The algorithm is classified as optimization and without optimization method that been used to simulate to find the weight fitness of chromosome which the input is intensified as air conditioning temperature and lighting illuminance (Lux). The methods are differs by the setting parameter of temperature of24°C and lighting of 500 Lux for optimization method, while 18°C air conditioning temperature and 540 Lux for without optimization method. A survey and questionnaire is carried out to 25 staffs and students to observe the impact before (without optimization) and after (optimization) the experiment is conducted. The results from GA indicates that the optimization method can save up to 18.04% in daily cost (counts in RM), 18% of power consumption (kWh) and 17.98% of current. The values is considered as success rate if the optimization is applied for the whole buildings in IKM Bintulu. Meanwhile, the survey shows that 63% agreed that the room temperature is set to default of24°C all day and 77% agreed the lighting illumination is set to 500 Lux. The survey concluded that 76% occupants are comfortable after the optimization method is implemented to the air conditioning system and lighting illuminance.